Enhanced thermal stability and ductility in a nanostructured Ni-based alloy. (December 2017) - Sun, Yanle; Fu, Liming; Fu, Zhiqiang; Shan, Aidang; Lavernia, Enrique J.
Abstract: In this investigation we address the question of whether it is possible to simultaneously enhance the ductility and thermal stability of nanostructured (NS) Ni-based alloy by using an approach that involves the introduction of nano-precipitates. To address this question, both NS and ultra-fine grained Ni-based alloys with nanoscale γ'-precipitates were obtained via heat treatment of single-phase NS Ni-based alloy ( 50 nm). Our results show that the thermally-stable γ'-precipitates contribute to both ductility and a remarkably high thermal stability close to 700 °C (0.62 T m ). The underlying mechanisms that are believed to be responsible for this behavior are discussed. Graphical abstract: